Production of added‐value metabolites by Yarrowia lipolytica growing in olive mill wastewater‐based media under aseptic and non‐aseptic conditions. Issue 6 (13th March 2017) - Sarris, Dimitris; Stoforos, Nikolaos G.; Mallouchos, Athanasios; Kookos, Ioannis K.; Koutinas, Apostolis A.; Aggelis, George; Papanikolaou, Seraphim
Abstract : Yarrowia lipolytica ACA‐YC 5033 was grown on glucose‐based media in which high amounts of olive mill wastewaters (OMWs) had been added. Besides shake‐flask aseptic cultures, trials were also performed in previously pasteurized media while batch bioreactor experiments were also done. Significant decolorization (∼58%) and remarkable removal of phenolic compounds (∼51% w/w ) occurred, with the latter being amongst the highest ones reported in the international literature, as far as yeasts were concerned during their growth on phenol‐containing media. In nitrogen‐limited flask fermentations the microorganism produced maximum citric acid quantity ≈19.0 g/L [simultaneous yield of citric acid produced per unit of glucose consumed (YCit/Glc )≈0.74 g/g]. Dry cell weight (DCW) values decreased at high phenol‐containing media, but, on the other hand, the addition of OMWs induced reserve lipid accumulation. Maximum citric acid concentration achieved (≈52.0 g/L; YCit/Glc ≈0.64 g/g) occurred in OMW‐based high sugar content media (initial glucose added at ≈80.0 g/L). The bioprocess was successfully simulated by a modified logistic growth equation. A satisfactory fitting on the experimental data occurred while the optimized parameter values were found to be similar to those experimentally measured. Finally, a non‐aseptic (previously pasteurized) trial was performed and its comparison with the equivalent aseptic experiment revealed no significant differences. Yarrowia lipolytica hence can be considered as a satisfactory candidate for simultaneous OMWs bioremediation and the production of added‐value compounds useful for the food industry.